ENTREPRENEURSHIP ORIENTATION BASED ON LOCAL CULTURAL VALUES AND PRODUCT INNOVATION TO IMPROVE MARKETING PERFORMANCE OF STRIPED FABRIC ARTICLES IN KRAPYAK WETAN, BANTUL, YOGYAKARTA - Dyah Ika Kirana Jalantina; Dewi Fatmasari (Sean Institute, 2022)
This study aims to analyze and describe in detail the entrepreneurial orientation based on local cultural values ​​and product innovation as an effort to improve marketing performance of lurik fabric craftsmen in Krapyak Wetan, Bantul, Yogyakarta. The analysis uses descriptive qualitative research methods with research instruments, namely interviews, direct observation and documentation. The results of the research analysis show that the development of the lurik craft business has ups and downs due to the decreasing number of skilled craftsmen using non-machine looms (ATBM), the application of entrepreneurial orientation based on local cultural values ​​can improve the marketing performance of lurik fabrics and requires craftsmen to always innovate. products, play an active role and are willing to take risks.